PENGARUH PENGADOPSIAN INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) TERHADAP KUALITAS INFORMASI AKUNTANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2013 - Hardita Juliyanti, 12.05.52.0036; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2016)
The study examines the effect of the adoption of International Financial Reporting Standards (IFRS) ob the quality of accounting information. The Sampling of this study is manufacturing companies listed in Bursa Efek Indonesia (BEI) in the period 2011-2013. The sampling method used purposive sampling. Influence between variable is described by using multiple linear regression analysis. The results indicate that the application of IFRS has positive effect and significant to the relevance adn reliability. Keywords: Quality of Accounting Information, IFRS, Relevane, Reliability